P400 Discordance in patient and physician perspectives and priorities in communication and management of ulcerative colitis: results of the European ulcerative colitis narrative survey. (25th January 2019) - Peyrin-Biroulet, L; Hart, A; Kayhan, C; Armuzzi, A; Schreiber, S
Abstract: Background: The ulcerative colitis (UC) narrative is a global survey of patients and gastroenterology physicians (GIs), aimed at identifying the impact of UC and comparing and contrasting perceptions of UC burden and management approaches. Here, we present data from a European survey of patients and GIs. Methods: Surveys were conducted online and by phone by The Harris Poll between August 2017 and February 2018. 1159 patients and 784 GIs in Finland, France, Germany, Italy, Spain and the UK completed the survey. Eligible adult patients with UC were those who had visited a GI in the previous 12 months and had ever received prescription medication for UC. Self-reported medication history was used as a proxy for disease severity, with patients with moderate to severe UC defined as patients who had ever taken immunosuppressants, tumour necrosis factor inhibitors, other biologics, or corticosteroids for >4 of the past 12 months. Patients who had only ever taken 5-aminosalicylates or had a colectomy were excluded. Mean age of patients was 39.9 years, 60% were male, and 84% had moderate-to-severe UC; 67% described their UC as controlled with few to no symptoms. Eligible GIs were those who saw ≥10 UC patients each month (of whom ≥10% were taking a biologic) and did not practise in a long-term care facility or hospice. GIs had been in speciality practice for a mean of 16.1 years and saw a mean of 43.4 patients with UC each month. Results: 86% of patients were very/somewhat satisfied with their current treatment; however, 74% wished they had more UC medication choices. Sixty-one per cent of patients wished their GI had discussed all available treatment options with them earlier, so they had a better idea of their choices; 74% of GIs wished they had more time for these discussions. The top indicators for considering changing medications were similar for patients and GIs: continued flares (38% of patients; 58% of GIs) and continued symptoms (31% of patients; 54% of GIs). The ability to manage symptoms was a top priority for patients and GIs for discussion at routine appointments; however, cancer risk was a pt priority, but not a GI priority (table). Discussion of treatment side effects at routine appointments was a GI priority (table). Both patients (68%) and GIs (81%) wish they had more time at appointments. Conclusions: Pts and GIs were in agreement regarding the symptoms leading to the consideration of changes in medication. Symptom control is a high priority for discussion among patients and GIs, but cancer risk was viewed as less of a priority for GIs. Shortage of appointment time was identified as a communication barrier.